Knowledge of Farmers about Improved Bt Cotton Production Technology - Manmeet Bishnoi ,S.S. Sisodiya , F.L. Sharma , Vinod Kumar, (Indian Journal of Extension Education, 2017)
This study was an attempt to get the response regarding knowledge of farmers about improved Bt cotton productiontechnology. A comprehensive list of all Bt cotton growers was prepared separately for all selected village ofidentified tehsil. Thereafter the farmers were categorized in to three categories i.e. large, small and marginal farmers.Following the procedure laid down above a sample of total 15 respondents i.e. 5 in each category from everyselected village were drawn randomly. Thus the study sample for the present investigation was comprised of 120respondents. (i.e. 60 from each tehsil) in all eight villages.